På skidor i kulturella gränsland : Samiska spår i skidsportens historia - Lidström, Isak (Malmö universitet, Institutionen Idrottsvetenskap (IDV), 2021)
The aim of this compilation thesis is to shed light on the Sámi history of ski sport in Sweden from an organizational and cultural history perspective where concepts like nation and ethnicity fill an important function. The Sámi are an indigenous people living in Sápmi, a land area extending across the North Calotte region and including parts of Norway, Sweden, Finland and Russia. The thesis contains six separate articles which together comprise a research period extending between 1879 and 1990. The articles have been studied from different points of view with the focus on how skis as sport equipment have been historically charged with cultural expressions created by the individual skiers as well as by the general public’s interest in skiing. These cultural expressions have also been internalized as collective identification objects positioning the mutual relations between groups and collectives. By historical links to kings, heroic myths and polar expeditions, the sport of skiing has, for example, become associated with a national Swedish identity. By pinpointing its Sámi origins in the light of history, the ski sport is in this thesis instead viewed as a culturally heterogeneous phenomenon. In three of the articles of the thesis, the Sámi history of Swedish ski sport is studied. The focus of these studies lies on how ”Sáminess” and ”Swedishness”, viewed as cultural identities, were constructed in connection with the early rise and development of ski sport from the late 19th century to the interwar period (Articles I and II) as well as with the sporting career of downhill skier Bengt-Erik Grahn in the 1960s (Article V). The studies illustrate that, at its rise and early development, cross-country skiing in Sweden was regarded as a Sámi sport. In the early 20th century, however, an ethnic borderline was created between what was Sámi and what was Swedish, which gradually invisibilized the Sámi link to ski sport. Instead, cross-country skiing acquired the inofficial character of being the Swedish national sport. ...